2022
DOI: 10.3389/fsufs.2021.771639
|View full text |Cite
|
Sign up to set email alerts
|

Processors' Experience in the Use of Flash Dryer for Cassava-derived Products in Nigeria

Abstract: This study was designed and carried out to ascertain the situation and perceptions of end users of cassava flash drying equipment in Nigeria with the aim of giving suggestions to policies and approaches for improved technology. Forty-one processing firms were selected and interviewed. Descriptive analyses were used and a logistic regression model was estimated. The results revealed that 49% of the firms stopped using their flash dryers due to the low demand for high-quality cassava flour (HQCF) resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…However, so far, there has been little use of the resulting models of locally built, small-scale flash dryers due to high energy consumption related to suboptimal design and consequently high production costs incompatible with market prices of final products. For instance, in Nigeria between 2006 and 2016, 157 cassava processors have invested in "first-generation" flash dryers to produce HQCF, most of which are no longer in use in spite of some improvements (Ojide et al 2021).…”
Section: Optimization Of Energy Efficiency For Drying Of Starch and F...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far, there has been little use of the resulting models of locally built, small-scale flash dryers due to high energy consumption related to suboptimal design and consequently high production costs incompatible with market prices of final products. For instance, in Nigeria between 2006 and 2016, 157 cassava processors have invested in "first-generation" flash dryers to produce HQCF, most of which are no longer in use in spite of some improvements (Ojide et al 2021).…”
Section: Optimization Of Energy Efficiency For Drying Of Starch and F...mentioning
confidence: 99%
“…In Nigeria, a recent survey of 41 HQCF processors to Fig. 4.1 Key components common to all flash-dryer designs ascertain current perceptions on flash dryers found that 50% of them have stopped producing in the past 10 years and that most see their market prospects as limited (Ojide et al 2021). Processors who remain in operation have done so through costsaving measures: being near the source of raw materials and the end-product market, thus cutting transportation costs; replacing petroleum-based fuels with more economical coal or agricultural biomass; and diversification to produce gari or fufu when there is no demand for HQCF.…”
Section: Surveys On Flash-dryer Designs and Energy Efficiencymentioning
confidence: 99%
“…By evaporation, drying removes moisture from solids to increase their shelf life, reduce transportation costs and make storage easier (Aghbashlo et al, 2008). The most energy-intensive process step in the production of high-quality cassava flour is drying, and keeping it under control is critical to ensuring the quality of the finished product (Tran et al, 2022) since the roots must be processed within 24 to 48 h of harvesting to reduce its toxicity and increase its shelf life, according to Ndaliman (2008). When cassava is processed into high-quality cassava flour, value is added to the product, its shelf life is extended, and transportation is made easier by the processing of cassava into high-quality cassava flour (Tran et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The most energy-intensive process step in the production of high-quality cassava flour is drying, and keeping it under control is critical to ensuring the quality of the finished product (Tran et al, 2022) since the roots must be processed within 24 to 48 h of harvesting to reduce its toxicity and increase its shelf life, according to Ndaliman (2008). When cassava is processed into high-quality cassava flour, value is added to the product, its shelf life is extended, and transportation is made easier by the processing of cassava into high-quality cassava flour (Tran et al, 2022). Drying is a common problem that small and medium-sized enterprises (SMEs) face when processing cassava starch (Suherman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation